Wall Street: on capitalism and the predatory instinct. Issue 3 (2nd October 2022) - Suchère, Thierry
ABSTRACT: Financial markets have a social history. In the 19th century, birth of capital markets led to the birth of the stock exchange novel, which inspired H de Balzac, E Zola, etc. During the 1980s, the financialization of the economy saw the cinema captured this change through the financial thriller. Oliver Stone's Wall Street (1987) inaugurates a list of recent movies that deals with the stock exchange. The film Wall Street shows us that financial activity allows rapid social ascension. The stock market activity is presented as a zero-sum game. Money simply passes from one pocket to another by the virtue of magic. The dynamic of capitalism thus finds part of their source in the greed of the individuals that it exploits. The market is the place where another form of economic rationality unfolds in the form of an instinct for predation which is not burdened by morality.